(untitled) (AmeriQuests, 2017)
Daniel J. Gervais, Restructuring Copyright : A Comprehensive Path to International Copyright Reform. Cheltenham, UK; Northampton, MA:Edward Elgar Publishing (Elgar Monographs in Intellectual Property Law), 2017, 359pp. ISBN: 978-1785369490